TRANSFER PRICING: DAMPAK BEBAN PAJAK, TUNNELING INCENTIVE, DAN PROFITABILITAS - Deden Tarmidi, SE., M.Ak., BKP.; Natalia Desy Novitasari (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2022)
This study was conducted to analysis impact of tax expense, tunneling incentives, and profitability on transfer pricing ratio. Used manufacturing companies listed on the Indonesia Stock Exchange in 2018-2020, this study uses multiple linear regression analysis with SPSS software. This study find that impact of tax expense and tunneling incentives as significantly on transfer pricing, while the profitability is have no significant impact. This shows that the magnitude of the tax burden can encourage management to increase transfer pricing transactions so that the tax burden on a consolidated basis is low, this is also reinforced by the impact of tunneling incentives that show the level of power ownership which also has an impact on transfer pricing transactions in minimizing the group company tax cost.